Extensive sensorimotor training predetermines central pain changes during the development of prolonged muscle pain - Zamorano, Anna; Kleber, Boris; Arguissain, Federico; Boudreau, Shellie; Vuust, Peter; Flor, Herta; Graven-Nielsen, Thomas (The journal of pain, 2023)
Repetitive movements (RM) are a main risk factor for musculoskeletal pain, which is partly explained by the overloading of musculoskeletal structures. However, RM may also drive brain plasticity, leading to maladaptive changes in sensorimotor areas and altered pain processing. This study aimed to understand whether individuals performing extensive RM (musicians) exhibit altered brain processing to prolonged experimental muscle pain. Nineteen healthy musicians and 20 healthy nontrained controls attended 3 sessions (Day 1-Day 3-Day 8). In each session, event-related potentials (ERPs) to non-nociceptive superficial and nociceptive intraepidermal electrical stimulation, reaction times, electrical detection thresholds, and pressure pain thresholds (PPTs) were recorded. In all participants, prolonged muscle pain was induced by intramuscular injection of nerve growth factor (NGF) into the right first dorsal interosseous muscle at the end of Day1. Pain intensity was assessed on a numerical rating scale (NRS) and was lower in musicians compared to non-musicians (P < .007). Moreover, in musicians, the higher amount of weekly training was associated with lower NRS pain scores on Day 3 to Day 8 (P < .037). Compared with Day1, NGF reduced PPTs on Day 3 to Day 8 (P < .001) and non-nociceptive P200 and P300 ERP amplitudes on Day 8 (P < .044) in both groups. Musicians compared to controls showed secondary hyperalgesia to electrical stimulation on Day 3 to Day 8 (P < .004) and reduced nociceptive P200 ERP amplitudes on Day 8 (P < .005). Across participants, ERP components correlated with pain detection reaction times, sensitivity (PPTs and electrical detection thresholds), and severity (NRS), (all P < .043). These results show that repetitive sensorimotor training leads to brain changes in the processing of prolonged pain, biasing the cortical response to nociceptive inputs. - Perspective - Repetitive sensorimotor training may increase the responsiveness of nociceptive inputs during the development of prolonged muscle pain. These novel data highlight the role of repetitive sensorimotor practice as a source for interindividual variability in central pain processing.